Layer-by-layer self-assembled energetic aluminum powder, preparation method and application thereof
By using layer-by-layer self-assembly technology to form a multi-layer cladding structure on the surface of aluminum powder, the energy efficiency reduction and combustion instability caused by aluminum powder alumina shell in the prior art is solved, and the energy density and combustion performance of aluminum powder are significantly improved.
Patent Information
- Application Number
- CN202310583185.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-05-23
AI Technical Summary
In the prior art, the presence of aluminum oxide shells in propellants and explosives leads to a longer ignition time, reduced energy efficiency, and uneven coating of fluoride, which affects combustion stability and combustion speed.
Through layer-by-layer self-assembly technology, components such as 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, boric acid and polyazidine glycidyl ether are used to form a multi-layered cladding structure on the surface of the aluminum powder to ensure uniform distribution of fluoride and adhesive, and improve the energy density and combustion performance of the aluminum powder.
It significantly improves the energy density and combustion performance of aluminum powder, reduces the ignition temperature, accelerates the energy release rate, increases the combustion speed of propellant and the energy density of explosives, and ensures stable storage and combustion of aluminum powder.
Smart Images

Figure CN116655441B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to layer-by-layer self-assembled energetic aluminum powder, a preparation method and application thereof, and belongs to the technical field of propellant fuel. Background Art
[0002] Aluminum powder is widely used in the field of explosives and propellants because of its high combustion calorific value, low price and rich energy storage. Pure aluminum powder is easily oxidized by air during the preparation process, forming a high melting point (2046℃) aluminum oxide shell on the surface of the aluminum powder. During the explosion of explosives or the combustion of propellants, the aluminum oxide shell will increase the ignition time and reduce the energy efficiency of aluminum powder, which will eventually lead to a decrease in the overall energy of explosives and propellants.
[0003] In order to reduce the ignition temperature of aluminum powder and improve its combustion efficiency, researchers usually use nanotechnology, ball milling and surface coating to modify aluminum powder. Nano aluminum powder has high reactivity but low effective aluminum content and low combustion heat. Although the ignition temperature of aluminum powder after ball milling is reduced, its morphology changes greatly, from spherical to flat, which is not conducive to the processing and application of solid propellants and explosives. The thermal decomposition products of fluoride can undergo a pre-ignition reaction with the alumina shell on the surface of aluminum powder, which can greatly accelerate the energy release rate of aluminum powder and reduce the agglomeration of aluminum powder during combustion. Therefore, fluoride is usually coated on the surface of aluminum powder to activate the aluminum powder.
[0004] In the prior art, the fluoride of the fluoride-coated aluminum powder composite is usually polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoropolyether (PFPE), fluoride salt or fluororubber, etc. Since the fluoride itself does not contain energy, the energy of the aluminum powder system will be reduced after the fluoride is coated alone. In addition, in the prior art, the fluoride-coated aluminum powder is often coated with solvent stirring evaporation, ultrasonic dispersion centrifugation and other means, which rely on the electrostatic force between organic matter and aluminum powder, which will make the fluoride not evenly distributed on the surface of the aluminum powder and cause the fluoride to fall off, affecting the stability and combustion effect of the aluminum powder combustion, and reducing the burning rate of the propellant. Summary of the invention
[0005] In order to overcome the defects of the prior art, one of the purposes of the present invention is to provide a layer-by-layer self-assembled energetic aluminum powder; the energetic aluminum powder has high energy, stable storage, and can increase the energy and burning rate of the propellant.
[0006] The second object of the present invention is to provide a method for preparing layer-by-layer self-assembled energetic aluminum powder. The preparation method is simple and easy to operate for layer-by-layer self-assembly. The fluoride and energetic adhesive in the prepared composite are evenly distributed on the surface of the aluminum powder, and the structure is stable.
[0007] The third object of the present invention is to provide an application of layer-by-layer self-assembled energetic aluminum powder, which can be used as a metal fuel for solid propellants or explosives to increase the energy of the explosives or solid propellants, and has good compatibility and dispersibility with other components of the solid propellants or explosives.
[0008] To achieve the purpose of the present invention, the following technical solutions are provided.
[0009] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0010] Micron aluminum powder 70%~90%,
[0011] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 3%~10%,
[0012] Boric acid 2%~6%,
[0013] Glycidyl azide polyether (GAP) 5%~14%;
[0014] The molecular weight of the polyazide glycidyl ether is less than or equal to 2000;
[0015] The auxiliary raw materials are a solvent and a hydrofluoric acid aqueous solution, and the solvent is tetrahydrofuran (THF) or anhydrous ethanol;
[0016] H,1H,2H,3H,3H-perfluorononane-1,2-diol forms a first coating layer on the surface of micron aluminum powder through the strong Al-F electronic force formed by hydrofluoric acid etching the aluminum oxide on the surface of the micron aluminum powder, boric acid forms a second coating layer by forming a dynamic borate ester bond with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, and polyazido glycidyl ether forms a third coating layer through the boron-nitrogen coordination effect with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, ultimately obtaining a layer-by-layer self-assembled energetic aluminum powder.
[0017] Preferably, the molecular weight of the polyazide glycidyl ether is 480-1000.
[0018] A method for preparing layer-by-layer self-assembled energetic aluminum powder according to the present invention, the method comprising the following steps:
[0019] (1) adding a solvent and a hydrofluoric acid aqueous solution into a reaction container, stirring and mixing them evenly, introducing an inert gas, and then adding micron aluminum powder and dispersing them evenly to obtain an aluminum suspension;
[0020] (2) completely dissolving 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in a solvent to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension, and then stirring for 3h to 5h to obtain a suspension;
[0021] (3) completely dissolving boric acid in a solvent to obtain a boric acid solution; then pouring the boric acid solution into the suspension, stirring at 50° C. to 65° C. for 2 h to 3 h, filtering, washing, and vacuum drying to obtain a preliminary product;
[0022] (4) pouring the preliminary product into a solvent, and then stirring for 10 min to 30 min to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether, stirring at 50° C. to 65° C. for 2 h to 3 h, filtering, washing, and vacuum drying to obtain a layer-by-layer self-assembled energetic aluminum powder;
[0023] Wherein, the solvent is tetrahydrofuran (THF) or anhydrous ethanol.
[0024] Preferably, in step (1), the ratio of the mass of the micron aluminum powder to the volume of the solvent is 1 g: 20 mL to 40 mL; the ratio of the micron aluminum powder to the hydrofluoric acid solution is 1 g: 2 to 4 mL; and the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 2% to 3%.
[0025] Preferably, in step (1), the stirring time is 10 min to 30 min.
[0026] Preferably, in step (2), stirring is performed at 50°C to 65°C for 3min to 6min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in the solvent; and the ratio of the mass of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol to the volume of the solvent is 1g:10mL~20mL.
[0027] Preferably, in step (3), the boric acid is completely dissolved in the solvent by stirring at 50°C to 65°C for 3min to 6min; and the ratio of the mass of boric acid to the volume of the solvent is 1g:10mL to 20mL.
[0028] Preferably, in step (3), anhydrous ethanol is used for washing; and vacuum drying is performed at 60° C. to 80° C. for 2 h to 4 h.
[0029] Preferably, in step (4), the ratio of the mass of the preliminary product to the volume of the solvent is 1 g: 10 mL to 20 mL.
[0030] Preferably, anhydrous ethanol is used for washing in step (4), and the vacuum drying is performed at 70° C. to 100° C. for 4 h to 6 h.
[0031] An application of the layer-by-layer self-assembled energetic aluminum powder of the present invention, wherein the layer-by-layer self-assembled energetic aluminum powder is used as a metal fuel for solid propellant or explosive.
[0032] Preferably, the solid propellant is HTPB propellant.
[0033] Beneficial Effects
[0034] (1) The present invention provides a layer-by-layer self-assembled energetic aluminum powder, in which an energetic binder polyazide glycidyl ether is introduced into the aluminum powder system. The exothermic enthalpy of the aluminum powder after coating is 2.05 times that of pure aluminum powder, which can significantly increase the energy of the aluminum powder system and increase the burning rate of the propellant; and the thermal decomposition products of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in the layer-by-layer self-assembled energetic aluminum powder can react with aluminum and aluminum oxide before the aluminum powder reaches the melting point, so that the aluminum powder undergoes a pre-ignition reaction, thereby reducing the ignition temperature of the aluminum powder, accelerating the energy release rate of the aluminum powder, and reducing the agglomeration of aluminum powder particles; different from the coating caused by electrostatic action of ordinary fluorides in the prior art, the chemical bridging effect of boric acid enables polyazide glycidyl ether and 1H,1H,2H,3H,3H-perfluorononane-1,2-diol to be firmly coated on the surface of the aluminum powder, so that the aluminum powder can be stably stored.
[0035] (2) The present invention provides a layer-by-layer self-assembled energetic aluminum powder, wherein the main raw materials of the energetic aluminum powder are micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, boric acid and polyazido glycidyl ether; 1H,1H,2H,3H,3H-perfluorononane-1,2-diol is coated on the surface of the micron aluminum powder by the strong Al-F electron force formed by etching the aluminum oxide on the surface of the micron aluminum powder with hydrofluoric acid, and the boric acid is then coated on the surface of the micron aluminum powder by forming a dynamic borate ester bond with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, and the polyazido glycidyl ether constructs a coating layer through the boron-nitrogen coordination effect with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, and then coats the micron aluminum powder, thereby obtaining a layer-by-layer self-assembled energetic aluminum powder.
[0036] (3) The present invention provides a layer-by-layer self-assembled energetic aluminum powder, wherein the auxiliary raw materials of the energetic aluminum powder are a solvent and an aqueous hydrofluoric acid solution, wherein the solvent is tetrahydrofuran or anhydrous ethanol; the aqueous hydrofluoric acid solution can etch away the aluminum oxide on the surface of the micron aluminum powder, promote the combustion of the aluminum powder, and the generated AlF3 can be filtered out with the solution; 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, boric acid and polyazido glycidyl ether have certain solubility in tetrahydrofuran and anhydrous ethanol, so tetrahydrofuran and anhydrous ethanol are selected as solvents.
[0037] (4) The present invention provides a method for preparing layer-by-layer self-assembled energetic aluminum powder, wherein the mass ratio of micron aluminum powder to 1H,1H,2H,3H,3H-perfluorononane-1,2-diol is 7-30:1. If the amount of micron aluminum powder is excessive, the surface of the aluminum powder cannot be completely coated with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, and subsequent boric acid and polyazido glycidyl ether cannot be coated. -Excessive amount of diol will cause coating accumulation, and a large amount of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol will appear in the solution, and the bonding force between the coating and the micron aluminum powder will deteriorate; excessive amount of boric acid will cause the solution to contain undissolved boric acid, seriously affecting the stability of the preparation process and causing the energy of the energetic aluminum powder system to decrease; excessive amount of polyazido glycidyl ether will fail to effectively form an energetic coating layer, resulting in a waste of polyazido glycidyl ether and a decrease in the density of the energetic aluminum powder.
[0038] (5) The present invention provides an application of layer-by-layer self-assembled energetic aluminum powder, wherein the layer-by-layer self-assembled energetic aluminum powder is used as a metal fuel in a solid propellant or an explosive; the azide group of the GAP group can increase the energy of the explosive or the solid propellant, and the binder in the solid propellant or the explosive has good compatibility and dispersibility; the close connection between 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, boric acid and polyazide glycidyl ether and the aluminum powder can increase the fatigue resistance of the solid propellant, which is not available in ordinary aluminum powder or ordinary fluoride-coated aluminum powder composites. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is the infrared spectra of micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product of Example 1.
[0040] Figure 2 The differential scanning calorimetry (DSC) curves of the micron aluminum powder and the final product of Example 1 are shown in FIG. DETAILED DESCRIPTION
[0041] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the present invention.
[0042] Micron aluminum powder was purchased from Shanghai Aladdin Reagent Co., Ltd. with spherical specifications, D50: 9~11μm, and purity ≥99.8%.
[0043] Example 1
[0044] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0045] Micron aluminum powder 70%,
[0046] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 10%,
[0047] Boric acid 6%,
[0048] Glycidyl azide polyether (GAP) 14%;
[0049] The auxiliary raw materials are hydrofluoric acid solution and tetrahydrofuran, and tetrahydrofuran is used as the solvent of the main raw material.
[0050] The method steps are as follows:
[0051] (1) Add tetrahydrofuran and hydrofluoric acid solution into a reaction container, stir for 10 minutes to mix them evenly, introduce inert gas, and then disperse micron aluminum powder therein to obtain an aluminum suspension;
[0052] The ratio of the mass (g) of micron aluminum powder to the volume (mL) of tetrahydrofuran is 1:20; the ratio of the micron aluminum powder to the hydrofluoric acid solution is 1g:2mL; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 3%;
[0053] (2) Stirring at 50°C for 6 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in tetrahydrofuran to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension, and then stirring for 3 h;
[0054] The ratio of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol mass (g) to tetrahydrofuran volume (mL) is 1:10;
[0055] (3) Stirring at 50°C for 3 minutes to completely dissolve the boric acid in tetrahydrofuran to obtain a boric acid solution; then pouring the boric acid solution into the aluminum suspension prepared in (2), and then stirring at 60°C for 2 hours, filtering the obtained aluminum suspension for the first time, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 60°C for 2 hours to obtain a preliminary product;
[0056] The ratio of the mass of boric acid (g) to the volume of tetrahydrofuran (mL) is 1:10;
[0057] (4) pouring the preliminary product obtained in (3) into tetrahydrofuran, and then stirring for 10 minutes to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether to the coated aluminum powder suspension, stirring at 60°C for 2 hours, filtering the obtained aluminum suspension, washing with anhydrous ethanol for 3 times, and vacuum drying at 70°C for 4 hours to obtain a layer-by-layer self-assembled energetic aluminum powder;
[0058] The ratio of the mass (g) of the preliminary product to the volume (mL) of tetrahydrofuran is 1:10; the molecular weight of polyazide glycidyl ether is 480.
[0059] The final product of Example 1 was subjected to a scanning electron microscope-energy spectrum test, and it was found that the elements C, N, O, and F were evenly distributed on the surface of the aluminum powder. Therefore, it can be determined that the final product of Example 1 is layer-by-layer self-assembled energetic aluminum powder.
[0060] Infrared spectroscopy was performed on micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product prepared in Example 1. The results are as follows: Figure 1 As shown in the figure, the infrared spectrum of micron aluminum powder is close to a straight line without peaks; 1H,1H,2H,3H,3H-perfluorononane-1,2-diol has a peak at 1197~1128cm -1 There is a CF characteristic peak at 2095 cm -1 There is a characteristic peak of N3 at the position, and the characteristic peak appears in the infrared spectrum of the final product of Example 1, indicating that 1H, 1H, 2H, 3H, 3H-perfluorononane-1,2-diol and polyazido glycidyl ether are present in the final product prepared in Example 1.
[0061] The micron aluminum powder and the final product of Example 1 were subjected to DSC testing, and the results were as follows: Figure 2 As shown, the exothermic enthalpy of pure aluminum powder at 690-1100°C is only 1.61 kJ / g, while the exothermic enthalpy of the final product of Example 1 is as high as 3.30 kJ / g, which is 2.05 times that of pure aluminum powder. This indicates that the fluoride encapsulating the micron aluminum powder in the composite itself contains energy and can be used as a metal fuel in solid propellants to increase the energy of the propellant.
[0062] An ignition test was conducted on the micron aluminum powder and the final product of Example 1. It was found that the flame height of the micron aluminum powder was only 2 cm, while the flame height of the final product of Example 1 was 10 cm, and the combustion performance was greatly improved.
[0063] The final product of Example 1 was added to HTPB propellant (HTPB / AP / layer-by-layer self-assembled energetic aluminum powder = 14 / 68 / 18 (mass ratio)), and a cyclic tensile test was carried out. The cyclic stress-strain curve showed that the fatigue resistance of the HTPB propellant added with the final product of Example 1 was improved, and the cyclic stretching could be performed 200 times. The HTPB propellant with pure aluminum powder as the metal fuel (HTPB / AP / Al = 14 / 68 / 18) broke after being stretched 150 times.
[0064] Example 2
[0065] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0066] Micron aluminum powder 90%,
[0067] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 3%,
[0068] Boric acid 2%,
[0069] Glycidyl polyazide (GAP) 5%;
[0070] The auxiliary raw materials are hydrofluoric acid solution and tetrahydrofuran, and tetrahydrofuran is used as the solvent of the main raw material.
[0071] The method steps are as follows:
[0072] (1) Add tetrahydrofuran and hydrofluoric acid solution into a reaction container, stir for 30 minutes to make them evenly mixed, introduce inert gas, and then disperse micron aluminum powder therein to obtain an aluminum suspension;
[0073] The ratio of the mass (g) of micron aluminum powder to the volume (mL) of tetrahydrofuran is 1:40; the ratio of the micron aluminum powder to the hydrofluoric acid solution is 1g:4ml; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 2%;
[0074] (2) Stirring at 50°C for 3 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in tetrahydrofuran to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension, and then stirring for 5 h;
[0075] The ratio of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol mass (g) to tetrahydrofuran volume (mL) is 1:20;
[0076] (3) Stirring at 50°C for 6 minutes to completely dissolve the boric acid in tetrahydrofuran to obtain a boric acid solution; then pouring the boric acid solution into the aluminum suspension prepared in (2), and then stirring at 65°C for 3 hours, filtering the obtained aluminum suspension for the first time, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 65°C for 4 hours to obtain a preliminary product;
[0077] The ratio of the mass of boric acid (g) to the volume of tetrahydrofuran (mL) is 1:20;
[0078] (4) pouring the preliminary product obtained in (3) into tetrahydrofuran, and then stirring for 30 minutes to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether to the coated aluminum powder suspension, stirring at 65°C for 3 hours, filtering the obtained aluminum suspension, washing with anhydrous ethanol for 3 times, and vacuum drying at 100°C for 6 hours to obtain a layer-by-layer self-assembled energetic aluminum powder;
[0079] The ratio of the mass (g) of the preliminary product to the volume (mL) of tetrahydrofuran is 1:20; the molecular weight of the polyazide glycidyl ether is 1000.
[0080] The final product of Example 2 was subjected to a scanning electron microscope-energy spectrum test, and it was found that the elements C, N, O, and F were evenly distributed on the surface of the aluminum powder. Therefore, it can be determined that the final product of Example 2 is layer-by-layer self-assembled energetic aluminum powder.
[0081] The infrared spectrum of micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product prepared in Example 2 was tested. The infrared spectrum of micron aluminum powder was approximately a straight line without peaks; the infrared spectrum of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol was 1197~1128cm -1 There is a CF characteristic peak at 2095 cm -1 There is a characteristic peak of N3 at the position, and the characteristic peak appears in the infrared spectrum of the final product of Example 2, indicating that 1H, 1H, 2H, 3H, 3H-perfluorononane-1,2-diol and polyazido glycidyl ether are present in the final product prepared in Example 2.
[0082] The DSC test was performed on the micron aluminum powder and the final product of Example 2. The exothermic enthalpy of pure aluminum powder at 690-1100°C was only 1.61 kJ / g, while the exothermic enthalpy of the final product of Example 2 was as high as 3.29 kJ / g, which is 2.04 times that of pure aluminum powder. This shows that the fluoride encapsulating the micron aluminum powder in the composite itself contains energy and can be used as a metal fuel in solid propellants to increase the energy of the propellant.
[0083] An ignition test was conducted on the micron aluminum powder and the final product of Example 2. It was found that the flame height of the micron aluminum powder was only 2 cm, while the flame height of the final product of Example 2 was 9 cm, and the combustion performance was greatly improved.
[0084] The final product of Example 2 was added to HTPB propellant (HTPB / AP / layer-by-layer self-assembled energetic aluminum powder = 14 / 68 / 18), and a cyclic tensile test was carried out. The cyclic stress-strain curve showed that the fatigue resistance of the HTPB propellant to which the final product of Example 2 was added was improved, and the cyclic stretching could be performed 205 times. The HTPB propellant with pure aluminum powder as the metal fuel (HTPB / AP / Al = 14 / 68 / 18) broke after being stretched 150 times.
[0085] Example 3
[0086] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0087] Micron aluminum powder 80%,
[0088] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 5%,
[0089] Boric acid 5%,
[0090] Glycidyl azide polyether (GAP) 10%;
[0091] The auxiliary raw materials are hydrofluoric acid solution and anhydrous ethanol, and the anhydrous ethanol is used as the solvent of the main raw material.
[0092] The method steps are as follows:
[0093] (1) Anhydrous ethanol and hydrofluoric acid solution are added to a reaction container, stirred for 20 minutes to make them evenly mixed, and an inert gas is introduced, and then micron aluminum powder is dispersed therein to obtain an aluminum suspension;
[0094] The ratio of the mass (g) of micron aluminum powder to the volume (mL) of anhydrous ethanol is 1:30; the ratio of micron aluminum powder to hydrofluoric acid solution is 1g:3ml; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 2.5%;
[0095] (2) Stirring at 65°C for 4 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in anhydrous ethanol to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension and stirring for 4 h;
[0096] The ratio of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol mass (g) to anhydrous ethanol volume (mL) is 1:15;
[0097] (3) Stirring at 65°C for 5 minutes to completely dissolve the boric acid in anhydrous ethanol to obtain a boric acid solution; then pouring the boric acid solution into the aluminum suspension prepared in (2), and then stirring at 50°C for 2.5 hours. The obtained aluminum suspension is initially filtered, washed with anhydrous ethanol for 3 times, and vacuum dried at 70°C for 3 hours to obtain a preliminary product;
[0098] The ratio of the mass of boric acid (g) to the volume of anhydrous ethanol (mL) is 1:15;
[0099] (4) pouring the preliminary product obtained in (3) into anhydrous ethanol, and then stirring for 30 minutes to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether to the coated aluminum powder suspension, stirring at 50°C for 3 hours, filtering the obtained aluminum suspension, washing with anhydrous ethanol for 3 times, and vacuum drying at 80°C for 5 hours to obtain layer-by-layer self-assembled energetic aluminum powder;
[0100] The ratio of the mass (g) of the preliminary product to the volume (mL) of anhydrous ethanol is 1:15; the molecular weight of polyazide glycidyl ether is 600.
[0101] The final product of Example 3 was subjected to a scanning electron microscope-energy spectrum test, and it was found that the elements C, N, O, and F were evenly distributed on the surface of the aluminum powder. Therefore, it can be determined that the final product of Example 3 is layer-by-layer self-assembled energetic aluminum powder.
[0102] The infrared spectrum of micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product prepared in Example 3 was tested. The infrared spectrum of micron aluminum powder was approximately a straight line without peaks; the infrared spectrum of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol was 1197~1128cm -1 There is a CF characteristic peak at 2095 cm -1There is a characteristic peak of N3 at the position, and the characteristic peak appears in the infrared spectrum of the final product of Example 3, indicating that 1H, 1H, 2H, 3H, 3H-perfluorononane-1,2-diol and polyazido glycidyl ether are present in the final product prepared in Example 3.
[0103] The DSC test was performed on the micron aluminum powder and the final product of Example 3. The exothermic enthalpy of pure aluminum powder at 690-1100°C was only 1.61 kJ / g, while the exothermic enthalpy of the final product of Example 3 was as high as 3.31 kJ / g, which was 2.06 times that of pure aluminum powder. This indicates that the fluoride encapsulating the micron aluminum powder in the composite itself contains energy and can be used as a metal fuel in solid propellants to increase the energy of the propellant.
[0104] An ignition test was performed on the micron aluminum powder and the final product of Example 3. It was found that the flame height of the micron aluminum powder was only 2 cm, while the flame height of the final product of Example 3 was 11 cm, and the combustion performance was greatly improved.
[0105] The final product of Example 3 was added to HTPB propellant (HTPB / AP / layer-by-layer self-assembled energetic aluminum powder = 14 / 68 / 18), and a cyclic tensile test was carried out. The cyclic stress-strain curve showed that the fatigue resistance of the HTPB propellant added with the final product of Example 3 was improved, and the cyclic stretching was performed for 192 times. The HTPB propellant with pure aluminum powder as the metal fuel (HTPB / AP / Al = 14 / 68 / 18) broke after being stretched for 150 times.
[0106] Example 4
[0107] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0108] Micron aluminum powder 85%,
[0109] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 6%,
[0110] Boric acid 4%,
[0111] Glycidyl azide poly(GAP) 5%;
[0112] The auxiliary raw materials are hydrofluoric acid solution and tetrahydrofuran, and tetrahydrofuran is used as the solvent of the main raw material.
[0113] The method steps are as follows:
[0114] (1) Add tetrahydrofuran and hydrofluoric acid solution into a reaction container, stir for 20 minutes to mix them evenly, introduce inert gas, and then disperse micron aluminum powder therein to obtain an aluminum suspension;
[0115] The ratio of the mass (g) of micron aluminum powder to the volume (mL) of tetrahydrofuran is 1:30; the ratio of the micron aluminum powder to the hydrofluoric acid solution is 1g:3ml; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 3%;
[0116] (2) Stirring at 55°C for 3 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in tetrahydrofuran to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension and stirring for 4 h;
[0117] The ratio of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol mass (g) to tetrahydrofuran volume (mL) is 1:20;
[0118] (3) Stirring at 55°C for 6 minutes to completely dissolve the boric acid in tetrahydrofuran to obtain a boric acid solution; then pouring the boric acid solution into the aluminum suspension prepared in (2), and then stirring at 55°C for 3 hours, filtering the obtained aluminum suspension for the first time, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 80°C for 2 hours to obtain a preliminary product;
[0119] The ratio of the mass of boric acid (g) to the volume of tetrahydrofuran (mL) is 1:20;
[0120] (4) pouring the preliminary product obtained in (3) into tetrahydrofuran, and then stirring for 30 minutes to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether to the coated aluminum powder suspension, stirring at 55°C for 3 hours, filtering the obtained aluminum suspension, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 80°C for 6 hours to obtain layer-by-layer self-assembled energetic aluminum powder;
[0121] The ratio of the mass (g) of the preliminary product to the volume (mL) of tetrahydrofuran is 1:20; the molecular weight of polyazide glycidyl ether is 760.
[0122] The final product of Example 4 was subjected to a scanning electron microscope-energy spectrum test, and it was found that the elements C, N, O, and F were evenly distributed on the surface of the aluminum powder. Therefore, it can be determined that the final product of Example 4 is layer-by-layer self-assembled energetic aluminum powder.
[0123] The infrared spectrum of micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product prepared in Example 4 was tested. The infrared spectrum of micron aluminum powder was approximately a straight line without peaks; the infrared spectrum of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol was 1197~1128cm -1There is a CF characteristic peak at 2095 cm -1 There is a characteristic peak of N3 at the position, and the characteristic peak appears in the infrared spectrum of the final product of Example 4, indicating that 1H, 1H, 2H, 3H, 3H-perfluorononane-1,2-diol and polyazido glycidyl ether are present in the final product prepared in Example 4.
[0124] The micron aluminum powder and the final product of Example 4 were subjected to DSC tests. The exothermic enthalpy of pure aluminum powder at 690-1100°C was only 1.60 kJ / g, while the exothermic enthalpy of the final product of Example 4 was as high as 3.28 kJ / g, which is 2.05 times that of pure aluminum powder. This indicates that the fluoride encapsulating the micron aluminum powder in the composite itself contains energy and can be used as a metal fuel in solid propellants to increase the energy of the propellant.
[0125] An ignition test was conducted on the micron aluminum powder and the final product of Example 4. It was found that the flame height of the micron aluminum powder was only 2 cm, while the flame height of the final product of Example 4 was 11 cm, and the combustion performance was greatly improved.
[0126] The final product of Example 4 was added to HTPB propellant (HTPB / AP / layer-by-layer self-assembled energetic aluminum powder = 14 / 68 / 18), and a cyclic tensile test was carried out. The cyclic stress-strain curve showed that the fatigue resistance of the HTPB propellant added with the final product of Example 4 was improved, and the cyclic stretching was 201 times. The HTPB propellant with pure aluminum powder as the metal fuel (HTPB / AP / Al = 14 / 68 / 18) broke after being stretched 150 times.
[0127] Example 5
[0128] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0129] Micron aluminum powder 75%,
[0130] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 10%,
[0131] Boric acid 6%,
[0132] Glycidyl azide polyether (GAP) 9%;
[0133] The auxiliary raw materials are hydrofluoric acid solution and anhydrous ethanol, and the anhydrous ethanol is used as the solvent of the main raw material.
[0134] The method steps are as follows:
[0135] (1) Anhydrous ethanol and hydrofluoric acid solution are added to a reaction container, stirred for 10 minutes to make them evenly mixed, and an inert gas is introduced, and then micron aluminum powder is dispersed therein to obtain an aluminum suspension;
[0136] The ratio of the mass (g) of micron aluminum powder to the volume (mL) of anhydrous ethanol is 1:20; the ratio of micron aluminum powder to hydrofluoric acid solution is 1g:2ml; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 3%;
[0137] (2) Stirring at 64°C for 6 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in anhydrous ethanol to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension and stirring for 5 h;
[0138] The ratio of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol mass (g) to anhydrous ethanol volume (mL) is 1:10;
[0139] (3) Stirring at 60°C for 4 minutes to completely dissolve the boric acid in anhydrous ethanol to obtain a boric acid solution; then pouring the boric acid solution into the aluminum suspension prepared in (2), and then stirring at 60°C for 3 hours, filtering the obtained aluminum suspension for the first time, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 70°C for 3 hours to obtain a preliminary product;
[0140] The ratio of the mass of boric acid (g) to the volume of anhydrous ethanol (mL) is 1:15;
[0141] (4) Pour the product obtained in (3) into anhydrous ethanol, and then stir for 30 minutes to obtain a coated aluminum powder suspension, add polyazide glycidyl ether to the coated aluminum powder suspension, stir at 65°C for 3 hours, filter the obtained aluminum suspension, wash it with anhydrous ethanol for 3 times, and vacuum dry it at 90°C for 5 hours to obtain layer-by-layer self-assembled energetic aluminum powder;
[0142] The ratio of the mass (g) of the product to the volume (mL) of anhydrous ethanol is 1:15; the molecular weight of polyazide glycidyl ether is 900.
[0143] The final product of Example 5 was subjected to a scanning electron microscope-energy spectrum test, and it was found that the elements C, N, O, and F were evenly distributed on the surface of the aluminum powder. Therefore, it can be determined that the final product of Example 5 is layer-by-layer self-assembled energetic aluminum powder.
[0144] The infrared spectrum of micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product prepared in Example 5 was tested. The infrared spectrum of micron aluminum powder was approximately a straight line without peaks; the infrared spectrum of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol was 1197~1128cm -1 There is a CF characteristic peak at 2095 cm -1 There is a characteristic peak of N3 at the position, and the characteristic peak appears in the infrared spectrum of the final product of Example 5, indicating that 1H, 1H, 2H, 3H, 3H-perfluorononane-1,2-diol and polyazido glycidyl ether are present in the final product prepared in Example 5.
[0145] The DSC test was performed on the micron aluminum powder and the final product of Example 5. The exothermic enthalpy of pure aluminum powder at 690-1100°C was only 1.62 kJ / g, while the exothermic enthalpy of the final product of Example 5 was as high as 3.32 kJ / g, which is 2.05 times that of pure aluminum powder. This shows that the fluoride encapsulating the micron aluminum powder in the composite itself contains energy and can be used as a metal fuel in solid propellants to increase the energy of the propellant.
[0146] An ignition test was conducted on the micron aluminum powder and the final product of Example 5. It was found that the flame height of the micron aluminum powder was only 2 cm, while the flame height of the final product of Example 5 was 10 cm, and the combustion performance was greatly improved.
[0147] The final product of Example 5 was added to HTPB propellant (HTPB / AP / layer-by-layer self-assembled energetic aluminum powder = 14 / 68 / 18), and a cyclic tensile test was carried out. The cyclic stress-strain curve showed that the fatigue resistance of the HTPB propellant added with the final product of Example 5 was improved, and the cyclic stretching was performed for 196 times. The HTPB propellant with pure aluminum powder as the metal fuel (HTPB / AP / Al = 14 / 68 / 18) broke after being stretched for 150 times.
[0148] Example 6
[0149] A layer-by-layer self-assembled energetic aluminum powder, wherein the raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material, and taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows:
[0150] Micron aluminum powder 83%,
[0151] 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol (PFND) 7%,
[0152] Boric acid 2%,
[0153] Glycidyl azide polyether (GAP) 8%;
[0154] The auxiliary raw materials are hydrofluoric acid solution and tetrahydrofuran, and tetrahydrofuran is used as the solvent of the main raw material.
[0155] The method steps are as follows:
[0156] (1) Add tetrahydrofuran and hydrofluoric acid solution into a reaction container, stir for 15 minutes to mix them evenly, introduce inert gas, and then disperse micron aluminum powder therein to obtain an aluminum suspension;
[0157] The ratio of the mass (g) of micron aluminum powder to the volume (mL) of tetrahydrofuran is 1:25; the ratio of the micron aluminum powder to the hydrofluoric acid solution is 1g:3ml; the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 3%;
[0158] (2) Stirring at 60°C for 3 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in tetrahydrofuran to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension, and then stirring for 4 h;
[0159] The ratio of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol mass (g) to tetrahydrofuran volume (mL) is 1:18;
[0160] (3) Stirring at 55°C for 5 minutes to completely dissolve the boric acid in tetrahydrofuran to obtain a boric acid solution; then pouring the boric acid solution into the aluminum suspension prepared in (2), and then stirring at 59°C for 2 hours, filtering the obtained aluminum suspension for the first time, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 70°C for 4 hours to obtain a preliminary product;
[0161] The ratio of the mass of boric acid (g) to the volume of tetrahydrofuran (mL) is 1:20;
[0162] (4) pouring the product obtained in (3) into tetrahydrofuran, and then stirring for 30 minutes to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether to the coated aluminum powder suspension, stirring at 60°C for 3 hours, filtering the obtained aluminum suspension, washing it with anhydrous ethanol for 3 times, and vacuum drying it at 100°C for 6 hours to obtain a layer-by-layer self-assembled energetic aluminum powder;
[0163] The ratio of the mass (g) of the initial product to the volume (mL) of tetrahydrofuran is 1:20; the molecular weight of polyazide glycidyl ether is 480.
[0164] The final product of Example 6 was subjected to a scanning electron microscope-energy spectrum test, and it was found that the elements C, N, O, and F were evenly distributed on the surface of the aluminum powder. Therefore, it can be determined that the final product of Example 6 is layer-by-layer self-assembled energetic aluminum powder.
[0165] The infrared spectrum of micron aluminum powder, 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, polyazide glycidyl ether and the final product prepared in Example 6 was tested. The infrared spectrum of micron aluminum powder was approximately a straight line without peaks; the infrared spectrum of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol was 1197~1128cm -1 There is a CF characteristic peak at 2095 cm -1 There is a characteristic peak of N3 at the position, and the characteristic peak appears in the infrared spectrum of the final product of Example 6, indicating that 1H, 1H, 2H, 3H, 3H-perfluorononane-1,2-diol and polyazido glycidyl ether are present in the final product prepared in Example 6.
[0166] The DSC test was performed on the micron aluminum powder and the final product of Example 6. The exothermic enthalpy of pure aluminum powder at 690-1100°C was only 1.61 kJ / g, while the exothermic enthalpy of the final product of Example 6 was as high as 3.31 kJ / g, which is 2.06 times that of pure aluminum powder. This shows that the fluoride encapsulating the micron aluminum powder in the composite itself contains energy and can be used as a metal fuel in solid propellants to increase the energy of the propellant.
[0167] An ignition test was performed on the micron aluminum powder and the final product of Example 6. It was found that the flame height of the micron aluminum powder was only 2 cm, while the flame height of the final product of Example 6 was 11 cm, and the combustion performance was greatly improved.
[0168] The final product of Example 6 was added to HTPB propellant (HTPB / AP / layer-by-layer self-assembled energetic aluminum powder = 14 / 68 / 18), and a cyclic tensile test was carried out. The cyclic stress-strain curve showed that the fatigue resistance of the HTPB propellant to which the final product of Example 6 was added was improved, and the cyclic stretching was performed for 192 times. The HTPB propellant with pure aluminum powder as the metal fuel (HTPB / AP / Al = 14 / 68 / 18) broke after being stretched for 150 times.
[0169] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A layer-by-layer self-assembled energetic aluminum powder, characterized in that: The raw materials of the energetic aluminum powder are composed of a main raw material and an auxiliary raw material. Taking the total mass of the main raw material as 100%, the components and their mass fractions are as follows: Micron aluminum powder 70%~90%, 1H,1H,2H,3H,3H-Perfluorononane-1,2-diol 3%~10%, Boric acid 2%~6%, Polyazide glycidyl ether 5%~14%; The molecular weight of the polyazide glycidyl ether is less than or equal to 2000; The auxiliary raw materials are solvent and hydrofluoric acid aqueous solution, and the solvent is tetrahydrofuran or anhydrous ethanol; H,1H,2H,3H,3H-perfluorononane-1,2-diol forms a first coating layer on the surface of micron aluminum powder through the strong Al-F electronic force formed by hydrofluoric acid etching the aluminum oxide on the surface of the micron aluminum powder, boric acid forms a second coating layer by forming a dynamic borate ester bond with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, and polyazido glycidyl ether forms a third coating layer through the boron-nitrogen coordination effect with 1H,1H,2H,3H,3H-perfluorononane-1,2-diol, ultimately obtaining a layer-by-layer self-assembled energetic aluminum powder.
2. The layer-by-layer self-assembled energetic aluminum powder according to claim 1, characterized in that: The molecular weight of the polyazide glycidyl ether is 480-1000.
3. A method for preparing layer-by-layer self-assembled energetic aluminum powder as claimed in claim 1 or 2, characterized in that: The method steps include: (1) adding a solvent and a hydrofluoric acid aqueous solution into a reaction container, stirring and mixing them evenly, introducing an inert gas, and then adding micron aluminum powder and dispersing them evenly to obtain an aluminum suspension; (2) completely dissolving 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in a solvent to obtain a 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution; then pouring the 1H,1H,2H,3H,3H-perfluorononane-1,2-diol solution into the aluminum suspension, and then stirring for 3h to 5h to obtain a suspension; (3) completely dissolving boric acid in a solvent to obtain a boric acid solution; then pouring the boric acid solution into the suspension, stirring at 50° C. to 65° C. for 2 h to 3 h, filtering, washing, and vacuum drying to obtain a preliminary product; (4) pouring the preliminary product into a solvent, and then stirring for 10 min to 30 min to obtain a coated aluminum powder suspension, adding polyazide glycidyl ether, stirring at 50° C. to 65° C. for 2 h to 3 h, filtering, washing, and vacuum drying to obtain a layer-by-layer self-assembled energetic aluminum powder; Wherein, the solvent is tetrahydrofuran or anhydrous ethanol.
4. The method for preparing the layer-by-layer self-assembled energetic aluminum powder according to claim 3, characterized in that: In step (1), the ratio of the mass of the micron aluminum powder to the volume of the solvent is 1 g: 20 mL to 40 mL; the ratio of the micron aluminum powder to the hydrofluoric acid aqueous solution is 1 g: 2 to 4 mL; and the mass fraction of hydrofluoric acid in the hydrofluoric acid aqueous solution is 2% to 3%.
5. The method for preparing the layer-by-layer self-assembled energetic aluminum powder according to claim 3, characterized in that: In step (2), the mixture is stirred at 50° C. to 65° C. for 3 min to 6 min to completely dissolve 1H,1H,2H,3H,3H-perfluorononane-1,2-diol in the solvent; the ratio of the mass of 1H,1H,2H,3H,3H-perfluorononane-1,2-diol to the volume of the solvent is 1 g:10 mL to 20 mL.
6. The method for preparing layer-by-layer self-assembled energetic aluminum powder according to claim 3, characterized in that: In step (3), the boric acid is completely dissolved in the solvent by stirring at 50°C to 65°C for 3min to 6min; the ratio of the mass of boric acid to the volume of the solvent is 1g:10mL to 20mL.
7. The method for preparing layer-by-layer self-assembled energetic aluminum powder according to claim 3, characterized in that: In step (4), the ratio of the mass of the preliminary product to the volume of the solvent is 1 g: 10 mL to 20 mL.
8. The method for preparing layer-by-layer self-assembled energetic aluminum powder according to claim 3, characterized in that: In step (1), the stirring time is 10 min to 30 min; In step (3), anhydrous ethanol is used for washing; vacuum drying is performed at 60°C to 80°C for 2h to 4h; In step (4), anhydrous ethanol is used for washing, and the vacuum drying is carried out at 70° C. to 100° C. for 4 h to 6 h.
9. An application of the layer-by-layer self-assembled energetic aluminum powder as claimed in claim 1 or 2, characterized in that: The layer-by-layer self-assembled energetic aluminum powder is used as a metal fuel for solid propellant or explosive.
10. The use of the layer-by-layer self-assembled energetic aluminum powder as claimed in claim 9, characterized in that: The solid propellant is HTPB propellant.
Citation Information
Patent Citations
Polyazide ether perfluorooctyl ester coated micron aluminum powder compound as well as preparation method and application thereof
CN115180997A
Passivated high-water-reactivity aluminum powder as well as preparation method and application thereof
CN116102386A